Endogenous ceramide phosphoethanolamine modulates circadian rhythm via neural–glial coupling in Drosophila. Issue 12 (27th July 2022) - Chen, Xiupeng; Li, Jie; Gao, Zhongbao; Yang, Yang; Kuang, Wenqing; Dong, Yue; Chua, Gek Huey; Huang, Xiahe; Jiang, Binhua; Tian, He; Wang, Yingchun; Huang, Xun; et al.
Abstract: While endogenous lipids are known to exhibit rhythmic oscillations, less is known about how specific lipids modulate circadian behavior. Through a series of loss-of-function and gain-of-function experiments on ceramide phosphoethanolamine (CPE) synthase of Drosophila, we demonstrated that pan-glial-specific deficiency in membrane CPE, the structural analog of mammalian sphingomyelin (SM), leads to arrhythmic locomotor behavior and shortens lifespan, while the reverse is true for increasing CPE. Comparative proteomics uncovered dysregulated synaptic glutamate utilization and transport in CPE-deficient flies. An extensive genetic screen was conducted to verify the role of differentially expressed proteins in circadian regulation. Arrhythmic locomotion under cpes 1 mutant background was rescued only by restoring endogenous CPE or SM through expressing their respective synthases. Our results underscore the essential role of CPE in maintaining synaptic glutamate homeostasis and modulating circadian behavior in Drosophila . The findings suggest that region-specific elevations of functional membrane lipids can benefit circadian regulation.